THE USE OF THE PENA E-BOOK (LEADERSHIP OF THE PROPHETMUHAMMAD SAW) AS MEDIA FOR ISLAMIC POLITICS LEARNINGIN ELEMENTARY SCHOOL - Fitriah Erza Nurrohmah; Universitas Pendidikan Indonesia, Sumedang; Anisa Rahma Salsabilla; Ani Nur Aeni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This article discusses the use of the PENA E-Book (Leadership of the Prophet Muhammad PBUH) as media for Islamic Politics learning in Elementary Schools. The aim of the study was to provide accurate information regarding the effectiveness of the PENA e-book(Leadership of the Prophet Muhammad PBUH) in increasing elementary students' understanding of the leadership of the Prophet Muhammad PBUH. The research method used is the Design & Development (D&D) method. The PENA E-Book (Leadership of the Prophet Muhammad PBUH) was tested on class IV students of SDN 1 Kebarepan. In addition, the material experts obtain an assessment of the media development. Based on the product assessment, validation was obtained from the material experts with an average percentage of 100% regarding the content of the material and media quality. The research results were goodbecause the assessment of Islamic Religious Education (PAI) teachers indicates an average percentage of 100%. It proves that the PENA E-Book (Leadership of the Prophet Muhammad PBUH) as Islamic Politics learning media in elementary schools is very suitable for use by students in elementary schools, especially as a medium that can assist teachers in conveying teaching materials to students.